Rotary fatigue life of NiTi alloy wires and FEA modelling of fatigue damage - Montalvão, Diogo (2020)
Nickel-Titanium (NiTi) alloys with superelastic properties have been increasingly introduced as a substitute to more conventional alloys. For example, NiTi alloys used in Dentistry, such as in Endodontic rotary files, possess superelastic properties that allow for the file to follow teeth root canals more easily than their stainless-steel counterparts. Nevertheless, during surgery, the file is subjected to cyclic bending loading, since it is spinning while being deformed inside the curved canal. Therefore, these instruments are prone to fracture due to fatigue, without showing any visible signals of degradation. This problem brought new challenges on how new instruments should be tested, as NiTi alloys are highly non-linear. However, most existing test setups ignore the fracture mechanics involved in the fatigue phenomenon. In this work, the results of rotary fatigue tests for NiTi wires from different manufacturers is presented. The formulation is described, where the material strength reduction can be quantified from the determination of the strain and the number of cycles until failure. Experimental tests as well as numerical Finite Element Analysis (FEA) simulations are presented to better understand the fatigue fracture mechanisms present in NiTi alloys, showing that there is good agreement between the predicted strains (difficult to measure in such small wires) and the cycles to failure. One characteristic is that these alloys exhibit a large hysteresis in the elastic domain if loaded up to the mixture of austenitic and martensitic phases (also known as B19’ martensite) and then unloaded. Rotating bending fatigue tests of NiTi wires show that, when loaded up to the B19’ martensite, the number of cycles to failure decrease with the applied strain.